PENERAPAN DIGITAL WATERMARK SEBAGAI VALIDASI KEABSAHAN GAMBAR DIGITAL DENGAN SKEMA BLIND WATERMARK - Adi Suheryadi (Jurnal Teknologi Terapan, 2017)
Digital watermarking is an important field of technological development that has now grown in the digital era. Digital era encourage the spread digital images on internet by the websites with a large scale. On the other hand, digital images are objects that are very easy to change or manipulate, and even copied irresponsibly. Meanwhile it is very difficult to prove the image has been changed by existing equipment at this time, and it is difficult to prove its ownership. This is an important issue, when the image is one of the evidences for legal cases, news reporting and medical filing, where the image must be ensured that the digital image is not subject to change or manipulation. In this paper, we present the application of digital watermarking to authentication and ownership validation of digital image so the image can be ascertained its validity. This research applies blind watermark scheme by using secret key that inserted at least-significant bits (LSB) of host image therefore the watermark is invisible watermark. The result of watermarked image has a small decrease in quality with the mean value of PSNR and MSE about 34.08 and 14.62.